Philosophy of Health Based on Local Wisdom of the Buton Tribe in Empowering HIV/AIDS Risk Populations in Baubau City: A Literature Review - Wa Ode Sitti Justin; Suryo Ediyono (Universitas Mandala Waluya, 2026)
HIV/AIDS remains a serious public health challenge, particularly among high-risk populations in Baubau City in the Southeast Sulawesi region of Indonesia. The Buton tribe has a long-standing tradition of local wisdom, which is encapsulated by the philosophical systems of Pobinci-Binciki Kuli (mutual empathy and social solidarity) and Bhinci-Bhinciki Kuli. These systems emphasize care, mutual respect and communal responsibility. This literature review explores how this philosophy can empower HIV/AIDS risk populations in Baubau City. A systematic literature review method was employed, involving a search of databases including Scopus, PubMed, and Google Scholar using keywords such as 'Buton tribe', 'local wisdom', 'HIV/AIDS', and 'health philosophy'. A total of 28 articles published between 2015 and 2025 met the inclusion criteria. The findings reveal that the Buton philosophical values of solidarity, non-discrimination, and communal care provide a culturally resonant foundation for HIV/AIDS prevention and care programmes. Integrating these values into peer education models and community health initiatives can significantly reduce stigma and increase health-seeking behaviour among at-risk populations. The review concludes that incorporating Buton local wisdom into public health strategies provides a sustainable and culturally sensitive approach to addressing HIV/AIDS in Baubau City.